BASIC ISSUES IN PRIMARY EDUCATION DELIVERY IN NIGERIA - Asodike, Juliana D.; Ikpitibo, Clinton L (European Scientific Journal, ESJ, 2014)
Education is widely regarded as the route to economic prosperity, the key to scientific and technological advancement, the means to combat unemployment, and the foundation of social equity. Based on this fact, the Federal Government of Nigeria like other developing countries has at different times made frantic efforts in increasing the number of children enrolled in primary schools though there are still many more who are not enrolled and who do not complete the programme. This massive expansion has been possible by the infusion of large sums of monetary allocation to primary education. Although the functionality of this level of education is not doubted, in addition to the structural changes made to improve the system, it has been saddled with problems ranging from issues of enrolment, funding, infrastructure, teaching personnel and curriculum provisions. This paper discusses the functionality of primary education and some of the structural changes made to meet the demands of the society. Furthermore, it highlights the earlier identified issues as they affect primary education delivery in Nigeria.